Chitin Synthesis and Degradation in Crustaceans: A Genomic View and Application - Zhang, Xiaojun; Yuan, Jianbo; Li, Fuhua; Xiang, Jianhai (Marine drugs, 2021)
Chitin is among the most important components of the crustacean cuticular exoskeleton and intestinal peritrophic matrix. With the progress of genomics and sequencing technology, a large number of gene sequences related to chitin metabolism have been deposited in the GenBank database in recent years. Here, we summarized the genes and pathways associated with the biosynthesis and degradation of chitins in crustaceans based on genomic analyses. We found that chitin biosynthesis genes typically occur in single or two copies, whereas chitin degradation genes are all multiple copies. Moreover, the chitinase genes are significantly expanded in most crustacean genomes. The gene structure and expression pattern of these genes are similar to those of insects, albeit with some specific characteristics. Additionally, the potential applications of the chitin metabolism genes in molting regulation and immune defense, as well as industrial chitin degradation and production, are also summarized in this review.